Pengaruh Material Sarung Tangan Anti Panas Pada Kenyamanan Pekerja Penggoreng Kerupuk di Pabrik Kerupuk Kapanewon Banguntapan - Sukmawati Sukmawati; Sri Puji Ganefati; Herman Santjoko; Haryono Haryono (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2026)
The cracker manufacturing industry poses safety and health hazards to its workers. One of the most hazardous areas in a cracker factory is the frying area. Based on a survey, the ambient temperature in the frying area was recorded at 31°C, while the oil temperature during frying reached 170°C. Approximately 80% of workers had experienced work-related accidents, primarily burns from hot oil splashes resulting in hand blisters. This situation is exacerbated by the fact that 100% of workers did not use gloves. The use of gloves is essential to protect workers, provided they are comfortable and do not introduce new hazards. The concept of comfort in using personal protective equipment (PPE) is defined as the worker feeling at ease and undisturbed while wearing PPE during work activities. Objective: To determine the effect of using various types of heat-resistant gloves on the comfort of cracker frying workers in cracker factories located in Kapanewon Banguntapan. Method: This study employed a quasi-experimental design using a post-test only group design, conducted in July 2024. By using a post-test design, the researcher aimed to measure the treatment effects without the influence of a pre-test. The study population comprised all cracker frying workers from three cracker factories in Kapanewon Banguntapan, totaling 30 individuals. Sampling was conducted using total sampling, meaning the entire population was included as the study sample. Data were analyzed using the Kruskal-Wallis statistical test. Results: The results showed that 13.5% of respondents reported comfort when using heat-resistant gloves made of fabric, 100% of respondents reported discomfort when using gloves made of fabric with corn husk lining, and 73% of respondents reported comfort when using gloves made of fabric with glasswool  lining. The Kruskal-Wallis test revealed a significant difference in comfort levels among the three types of heat-resistant gloves used (p-value = 0.000). Conclusion: Heat-resistant gloves made of fabric with a glasswool  lining were found to be the most comfortable for cracker frying workers in the Kapanewon Banguntapan area. Methodological Limitations:This study had several methodological limitations, including: (1) The experiment was conducted at different locations and times, preventing simultaneous treatment and potentially affecting the consistency of implementation; (2) Glove thickness varied across groups, which may have influenced comfort perception; (3) The use of different glove colors may have introduced visual bias; (4) The corn husk-lined gloves had a stiff texture due to the absence of a softening extraction process, thus not reflecting the material’s optimal potential; (5) Temperature measurements were conducted in only one experimental setting, failing to capture the full environmental variation; and (6) No follow-up observation was conducted on workers’ hand conditions post-use, thereby limiting the ability to assess long-term effects